Capacity Development for smallholder Irrigation in Kenya - Mati, Bancy M. (Published online in Wiley InterScience (www.interscience.wiley.com), 2008)
This paper presents the experiences on capacity development for irrigation in Kenya, drawing from a study of sevensmallholder irrigation schemes, namely: New Mutaro, Emening, Mitunguu, Ng’uuru Gakirwe, Lari, Mukuria-Kyambogo and Isiolo River Water Users Association. These schemes were selected for their apparent success inirrigation management, sustainability and poverty reduction among the beneficiaries. Although the seven schemeshad diverse innovations and enterprises, common drivers of success were identified as: (i) introduction of newknowledge/technology, (ii) availability of markets, (iii) good governance structures, (iv) funding for infras tructuredevelopment, and (v) targeted capacity development. It was also found that initial investment costs for smallholderirrigation schemes ranged from about US $198 to $1744 per ha, which is much lower than reported for large publicschemes. Generally, all the schemes had recorded im proved food security and incomes, with net earnings rangingfrom US $200 to $1200 per month for single-crop ente rprises. Capacity development had played a major role in thepositive performance of the schemes. However, the respective schemes had experienced different modes ofcapacity building, which included government extension services, NGOs, private sector, research institutes,out-grower support schemes and farmer-to-farmer learning. This paper focuses on the role of capacity develop-ment. Copyright # 2008 John Wiley & Sons, Ltd
Full text
Keywords: smallholder irrigation; capacity development; poverty reduction; Kenya